Schistosomiasis-associated pulmonary hypertension unveils disrupted murine gut–lung microbiome and reduced endoprotective Caveolin-1/BMPR2 expression - Marinho, Ygor; Villarreal, Elizabeth S.; Aboagye, Sammy Y.; Williams, David L.; Sun, Jun; Silva, Claudia L. M.; Lutz, Sarah E.; Oliveira, Suellen D. (Frontiers in Immunology, 2023)
Schistosomiasis-associated Pulmonary Arterial Hypertension (Sch-PAH) is a life-threatening complication of chronic S. mansoni infection that can lead to heart failure and death. During PAH, the expansion of apoptosis-resistant endothelial cells (ECs) has been extensively reported; however, therapeutic approaches to prevent the progression or reversal of this pathological phenotype remain clinically challenging. Previously, we showed that depletion of the anti-apoptotic protein Caveolin-1 (Cav-1) by shedding extracellular vesicles contributes to shifting endoprotective bone morphogenetic protein receptor 2 (BMPR2) towards transforming growth factor beta (TGF-β)-mediated survival of an abnormal EC phenotype. However, the mechanism underlying the reduced endoprotection in PAH remains unclear. Interestingly, recent findings indicate that, similar to the gut, healthy human lungs are populated by diverse microbiota, and their composition depends significantly on intrinsic and extrinsic host factors, including infection. Despite the current knowledge that the disruption of the gut microbiome contributes to the development of PAH, the role of the lung microbiome remains unclear. Thus, using a preclinical animal model of Sch-PAH, we tested whether S. mansoni infection alters the gut–lung microbiome composition and causes EC injury, initiating the expansion of an abnormal EC phenotype observed in PAH. Indeed, in vivo stimulation with S. mansoni eggs significantly altered the gut–lung microbiome profile, in addition to promoting injury to the lung vasculature, characterized by increased apoptotic markers and loss of endoprotective expression of lung Cav-1 and BMPR2. Moreover, S. mansoni egg stimulus induced severe pulmonary vascular remodeling, leading to elevated right ventricular systolic pressure and hypertrophy, characteristic of PAH. In vitro, exposure to the immunodominant S. mansoni egg antigen p40 activated TLR4/CD14-mediated transient phosphorylation of Cav-1 at Tyr14 in human lung microvascular EC (HMVEC-L), culminating in a mild reduction of Cav-1 expression, but failed to promote death and shedding of extracellular vesicles observed in vivo. Altogether, these data suggest that disruption of the host-associated gut–lung microbiota may be essential for the emergence and expansion of the abnormal lung endothelial phenotype observed in PAH, in addition to S. mansoni eggs and antigens.